Busana Pengantin Muslim Sebagai Media Komunikasi Dakwah di Kalangan Para Wanita Muslimah - Endivi Reksi Novrinta Reksi Novrinta; Agus Naryoso; Hedi Pudjo Santosa (Interaksi Online, 2021)
There are many things that can be used as a medium for preaching, one of which is preaching through Muslim wedding clothing. Unfortunately, currently there are many models of Muslim wedding dresses that have come out of their essence, thus obscuring the values and mission of da'wah. The existence of Muslim wedding dresses that are not in accordance with the Shari'ah are trying to be minimized by Muslim designers, they are trying to present and reintroduce Muslim wedding dresses that are in accordance with Islamic rules. This study aims to determine the use of Muslim wedding attire as a medium of da'wah communication and to examine the meaning of the use of Muslim wedding attire. This research is a qualitative research that uses non-verbal theory and cultural hermeneutic theory with a phenomenological approach. The data collection method used was in-depth interviews, with a total of 4 informants. Based on the results of the study, it was found that (1) Muslim wedding dress is a wedding dress whose model is adapted to the dress code in the Qur'an and Sunnah. With the criteria of a loose dress, not tight, not wasting material, not using excessive accessories, and wearing a long hijab that covers the chest. This is what distinguishes it from ordinary Muslim wedding dresses in general. (2) The non-verbal message contained in the Muslim wedding dress implies that a woman who wears a syar'i dress in her marriage is a woman who is obedient to her religious orders, a woman who is closed, always takes care of herself, and tries to get the title of a pious woman. (3) The more obedient a person carries out religious orders, especially in wearing clothes according to the rules they have, the more visible the quality of that person's religion will be. (4) Muslim bridal clothing can be used as a medium of da'wah communication. Da'wah with the media of Muslim bridal clothing is included in the da'wah bil haal, namely preaching through morals, namely exemplifying good behavior to someone. Its existence is often the center of public attention and is used in front of many audiences, making it easier to carry out da'wah missions to introduce Muslim wedding dress models to the public